The Implementation of the Team Games Tournament Learning Model to Improve Indonesian Language Learning Interest Among Elementary School Students - Andi Nur Zam-Zam; Nur Ilmi; Natriani Syam (PT. Lontara Digitech Indonesia, 2025)
Penelitian ini dilatarbelakangi oleh rendahnya minat belajar siswa di kelas V This study aims to improve the Indonesian language learning process and students’ learning interest through the implementation of the Team Games Tournament learning model in Grade V of UPTD SD Negeri 28 Parepare. This study used a qualitative approach with Classroom Action Research as the research design. The subjects of this study were 30 fifth-grade students, consisting of 17 male students and 13 female students, and one classroom teacher. The research was conducted in two cycles, and each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observation, questionnaires, and documentation. The data were analyzed using data condensation, data presentation, and conclusion drawing. The results showed that the implementation of the Team Games Tournament model improved both the learning process and students’ learning interest. In Cycle I, teacher activity reached 66% and student activity also reached 66%, both categorized as fair. Students’ learning interest in Cycle I reached 49.47%, which was categorized as low. After improvements were made in Cycle II, teacher activity increased to 86% and student activity increased to 84%, both categorized as good. Students’ learning interest also increased to 76.14%, which was categorized as very high. These findings indicate that the Team Games Tournament learning model can create a more active, enjoyable, and meaningful learning process. Therefore, this model can be used as an alternative strategy to improve students’ learning interest in Indonesian language learning, especially in pantun material at the elementary school level.